2014
DOI: 10.1002/chem.201402822
|View full text |Cite
|
Sign up to set email alerts
|

Phosphathiahelicenes: Synthesis and Uses in Enantioselective Gold Catalysis

Abstract: Enantiomerically pure thiahelicenes displaying a terminal phosphole unit and a stereogenic phosphorus center have been prepared by oxidative photocyclization of a diaryl-olefin precursor. Starting from one of these phosphathiahelicene oxides, the corresponding trivalent phosphine-Au(I) complex is obtained with complete diastereoselectivity. It affords a new, excellent precatalyst for the enantioselective cycloisomerization of N-tethered enynes (up to 96 % ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Thus, chromatographically separated endo-76 effectively catalyzes the enantioselective cycloisomerization of N-tethered 1,6-enyne 78 to give bicyclo[4.1.0]heptane 79 with 95% yield and 81% ee, whilst exo-77 remained almost inactive [56] (Scheme 12). Meanwhile, various phosphole-containing ligands were also prepared and screened in similar reactions with success [8,9,57]. Scheme 11.…”
Section: Scheme 11mentioning
confidence: 99%
“…Thus, chromatographically separated endo-76 effectively catalyzes the enantioselective cycloisomerization of N-tethered 1,6-enyne 78 to give bicyclo[4.1.0]heptane 79 with 95% yield and 81% ee, whilst exo-77 remained almost inactive [56] (Scheme 12). Meanwhile, various phosphole-containing ligands were also prepared and screened in similar reactions with success [8,9,57]. Scheme 11.…”
Section: Scheme 11mentioning
confidence: 99%
“…Thus, helicenes can be utilized them a broad range of applications in chiral materials, in the chiral recognition of biomolecules, and in asymmetric synthesis161718192021222324. More specifically, chiral helicene-based trivalent phosphorus ligands are efficient asymmetric inductors in metal-catalyzed asymmetric reactions and show good to excellent enantioselectivities252627282930313233. We hypothesized that novel helicenylphosphine ligands, which induce intramolecular metal-arene interactions, could be used to construct an efficient chiral catalytic system.…”
mentioning
confidence: 99%
“…A creative strategy for enantioenriched tetrahydropyridines via enyne cycloisomerization was outlined by Voituriez et al, through the use of a helically chiral gold phosphine catalyst as shown in Scheme 25 [105]. A related class of ligands, phosphathiahelicenes, was also used for this transformation, allowing for even higher enantioselectivities with some substrates [106].…”
Section: Intramolecular Cyclizationsmentioning
confidence: 98%